The Influence of Transformational Leadership and Job Characteristics on Absenteeism Among Telecommunication Company Employees in Yemen - Belhaj, Fozi Ali Salem (2012)
The objective of the study was to determine the influence of transformational leadership and job characteristics on absenteeism among 266 employees in telecommunication companies in Yemen. Additionally, this study was aimed to identifying the significance of psychological empowerment as a plausible mediator on the relationship between transformational leadership, job characteristics and absenteeism. Considering the importance of understanding the absenteeism phenomenon, it is valuable to increase insight into the factors that contribute to reduce absenteeism behavior. In this study, transformational leadership, job characteristics and psychological empowerment introduced as factors that may influence employee absenteeism in telecommunication companies. For purpose of data analysis and hypotheses testing several statistical methods such as multiple regression analysis were utilized to understand the dimensionality of the variables. The results of this study reported that idealized influence of transformational leadership and task significance of job characteristics were negatively influenced employee absenteeism. Psychological empowerment was also found to have a negative impact on absenteeism of employees in this study. The regression results also indicated that job characteristics (task significance and task identity) were found to have a positive influence on psychological empowerment, while transformational leadership (idealized influence and intellectual stimulation) were found to have no effect on psychological empowerment. The results of hierarchical multiple regression indicated that psychological empowerment found to be a significant mediating factor for the relationship between task significance of job characteristics and employee absenteeism in telecommunication companies.The relationship between transformational leadership, job characteristics, psychological empowerment and absenteeism suggested that it may be beneficial to the management of telecommunication companies to reduce absenteeism behavior. Based on research findings, theoretical and practical implications were discussed. Limitations and recommendations for future research were also highlighted